Математичне моделювання та чисельний аналіз двофазної фільтрації газу та рідини в пористому середовищі - Вавричук, Петро Григорович (Центр математичного моделювання Інституту прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, 2018)
Дисертація присвячена математичному моделюванню процесів фільтрації газу та води в пористих середовищах та розробленню методів знаходження параметрів роботи підземного сховища газу за наявності водного фактору. У роботі розв'язано задачу науково-технічного характеру в галузі математичного моделювання та обчислювальних методів. При дослідженні процесу фільтрації газу та води в пористих середовищах було вперше побудовано: математичну модель роботи підземного сховища газу (ПСГ) при наявності підошовної води та законтурної води; математичну модель для оцінки кількості дифундованого газу у воду при роботі ПСГ; математичну модель для оцінки швидкості руху газоводяного контакту з метою недопущення заводнення свердловини. Адаптовано чисельно-аналітичні ітераційні методи для розв’язування вище поставлених задач. Отримані теоретичні результати дали змогу дослідити параметри (дебіт свердловини, тиск на газозбірному пункті, пластовий тиск та швидкість підняття газоводяного контакту), які впливають на роботу ПСГ за наявності водного фактору, та корегувати їх відповідно для покращення роботи ПСГ. Диссертация посвящена математическому моделированию процессов фильтрации газа и воды в пористых средах и разработке методов нахождения параметров работы подземного хранилища газа при наличии водного фактора. В работе решена задача научно-технического характера в области мате-матического моделирования и вычислительных методов. При исследовании процесса фильтрации газа и воды в пористых средах впервые построено: математическую модель работы подземного хранилища газа (ПХГ) при наличии подошвенной и законтурной воды; математическую модель для оценивания количества дифундованого газа в воду при работе ПХГ; математическую модель для оценивания скорости движения газоводяного контакта с целью недопущения заводнения скважины. Адаптированы численно-аналитические итерационные методы для решения вышепоставленных задач. Полученные теоретические результаты позволили исследовать параметры (дебит скважины, давление на газосборном пункте, пластовое давление и скорость поднятия газоводяного контакта) при наличии водного фактора, которые влияют на работу ПХГ, и соответственно корректировать их для улучшения работы ПХГ. The presented work is devoted to mathematical modelling filtration processes of gas and water in porous medium and development of finding parameters methods of an underground gas storage work in the presence of water factor. The task of the scientific and technical character in the field of mathematical modeling and computational methods is solved. While creating and using underground gas stores (UGS) one of the main questions is establishing of functioning parameters for the underground gas store for maintenance of gas extraction process (gas flooding) in case the water is present in formations. Presence of water is detected almost in all gas stores (deposits) created in the depleted fields. Notwithstanding the great amount of the researches, currently no sufficient theory for describing of processes taking place in formations-collectors of gas stores with edge water has been yet proposed. Calculating UGS functioning parameters is getting complicated also due to the uncertainty of the porous medium parameters and its non-homogeneousness. This demands building of the corresponding adaptation models and methods, which allow specification of model parameters in accordance with the measured parameters (pressure, discharge, etc.). To construct the model of gas-water or water-gas displacement in the process of filtration in porous media and motion of two-phase mixtures in vertical wells and sloping areas of pipelines, it is necessary to take into account a lot of dynamic parameters. Despite the large number of studies in this field, there is no comprehensive theory to describe these processes so far. The calculation of filtration and motion of two-phase systems is even more complicated due to the uncertain parameters of porous media and their heterogeneity. In the study of the process of filtration of gas and water in porous media was first built: the ma-thematical model of the work of UGS in the presence of plantar water and water flow; the mathematical model for estimating the amount of diffused gas in water during operation of UGS; the mathematical model for estimating the speed of the gas-water contact in order to prevent flooding of the well. Numerical-analytical iterative methods for solving the above tasks are adapted. Recommendations concerning the operation of UGS in the presence of water factor are proposed. Mathematical model of such a process is being built. Functional connection between the mass flowrate and pressure values in the main gas pipeline and on the outer water edge is being established. Formulas for calculating of the main UGS functioning parameters during the process of gas extraction are obtained. Model problem and formulas for calculating underground gas store parameters are tested during multiple experiments.
Математическое моделирование и численный анализ двухфазной фильтрации газа и жидкости в пористой среде
Mathematical modeling and numerical analysis of two-phase filtration of gas and water in a porous medium
Keywords: математичне моделювання; фільтрація газу та води; пористе середовище; дифузія; конвекція; підземне сховище газу; газоводяний контакт; газозбірний пункт; математическое моделирование; фильтрация газа и воды; пористая среда; диффузия; конвекция; подземное хранилище газа; газоводяной контакт; газосборный пункт; mathematical modelling; filtration of gas and water; porous medium; diffusion; convection; underground gas storage; gas-water contact; gas collection point; 621.532.3.004.17:681.142:622.691.24:536.12